Replication data for: Consumer preferences and market segmentation for differentiated beef with less environmental impact - Enciso, Karen; Burkart, Stefan (International Center for Tropical Agriculture, 2020)
The aim of this study was to define consumer segments interested in purchasing beef with less environmental impact (derived from production systems with improved forages) and to determine their willingness to pay (WTP) for such products. A semi-structured questionnaire was applied to a total of 354 randomly selected meat consumers in Cali (Valle del Cauca Department), Popayán (Cauca Department) and in the Municipalities of Mercaderes and Patía (both Cauca Department) in Colombia.